Distribution and clinical association of plasma soluble ST2 during the development of type 2 diabetes. (August 2016) - Lin, Ya-Hui; Zhang, Rong-Cheng; Hou, Li-Bo; Wang, Kai-Juan; Ye, Zhong-Ni; Huang, Tao; Zhang, Jian; Chen, Xi; Kang, Jin-Suo
Highlights: Dynamic changes of sST2 levels during the development of diabetes were investigated. Elevated sST2 levels were associated with metabolic characteristics of diabetes. sST2 levels in the third and fourth quartiles increase risk of having diabetes. Abstract: Aim: ST2 plays important roles in diabetes and cardiovascular diseases. However, the distribution and changes in plasma soluble ST2 during the development of type 2 diabetes remain unclear. Methods: In the present study, 525 subjects were recruited and divided into three groups: normal, prediabetic and diabetic subjects. The sST2 levels of all subjects were measured using a high-sensitivity assay. Results: sST2 levels were modestly but significantly elevated in patients with diabetes (26.1 ng/ml) compared with normal subjects (19.3 ng/ml, P < 0.001) and persons with prediabetes (20.3 ng/ml, P < 0.001). The third and fourth quartiles (21.3 and 29.1 ng/ml, respectively) of the sST2 levels were associated with a 2.31- and 4.00-fold increased risk of having diabetes. With the prediabetic group as a reference population, patients with sST2 levels in the fourth quartiles had a higher increased risk of having diabetes mellitus (odds ratios = 2.19, P < 0.05). Furthermore, each SD log sST2 was associated with a 1.57-fold increased risk of atherosclerosis when all relevant variables was added to the multivariable logistic regression models. After adjustment for age and sex, all markers of liver and renal function, HDL-cholesterol, total cholesterol and smoking status showed a significant association with sST2 levels. Conclusion: Elevated sST2 levels were not only associated with metabolic characteristics of diabetes but also with a significantly increased risk of having diabetes.